Association of the ideal cardiovascular behaviors and factors with the incidence of nonalcoholic fatty liver disease: a prospective study. Issue 5 (May 2018) - Zhu, Shengtao; Shi, Jihong; Ji, Chunpeng; Yang, Guang; Xing, Jie; Zhu, Feng; Lin, Liming; Xing, Aijun; Huang, Zhe; Zhu, Chenrui; Wei, Xiaoming; Zhang, Shutian; et al.
Abstract : Objective: This study aimed to investigate the association of ideal cardiovascular behaviors and factors with the incidence of nonalcoholic fatty liver disease (NAFLD) prospectively. Patients and methods: We analyzed 25 278 (21 433 men and 11 895 women) participants in the study. Participants were divided into four categories according to the number of ideal cardiovascular behaviors and factors: 0–2, 3, 4, and 5–7 groups. Multivariate logistic regression was used to calculate the odds ratios with 95% confidence intervals (CIs). Results: After adjustment for confounding factors, the multivariate logistic regression model showed that the risk of NAFLD among the groups with 3, 4, 5–7 ideal factors was lower than the 0–2 group; after adjustment for age, sex, income, education level, and other confounders, the odds ratios were 0.74 (95% CI: 0.68–0.80), 0.49 (95% CI: 0.45–0.53), and 0.37 (95% CI: 0.33–0.41), respectively. Conclusion: The incidence of NAFLD decreased gradually with increasing ideal cardiovascular health behaviors and factors.